Translation and Social Media Communication in the Age of the Pandemic - Lee, Tong King; Wang, Dingkun (Routledge Focus on Translation and Interpreting Studies, 2022)
This collection of essays represents the first of its kind in exploring the conjunction of translation and social media communication, with a focus on how these practices intersect and transform each other against the backdrop of the cascading COVID-19 crisis. The contributions in the book offer empirical case studies as well as personal reflections on the topic, illuminating a broad range of themes such as knowledge translation, crisis communications, language policies, cyberpolitics and digital platformization. Together they demonstrate the vital role of translation in the trust-based construction of global public health discourses, while accounting for the new medialities that are reshaping the conception, experience and critique of translation in response to the cultural, political and ecological challenges in the post-pandemic world. Written by leading scholars in translation studies, media studies and literary studies, this volume sets to open up new conversations among these fields in relation to the global pandemic and its aftermath.